2002
DOI: 10.1046/j.1460-9568.2002.01894.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic bHLH transcription factors are novel candidates in the regulation of energy balance

Abstract: The basic helix–loop–helix transcription factors, neurological basic‐helix–loop–helix‐2 (Nhlh‐2), neurogenic differentiation‐1 (NeuroD‐1) and single minded‐1 (Sim‐1) could have roles in energy balance regulation, although supporting evidence is inconclusive. This study in mice provides further evidence that Nhlh‐2 and NeuroD‐1 are involved in energy balance regulation. In situ hybridization was used to study the expression of the genes in relation to physiological status and genetic background within hypothala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 36 publications
(44 reference statements)
4
24
0
Order By: Relevance
“…All these regions also express Mc4r (23). Previous studies that did not report Sim1 expression outside the PVN and SON used less sensitive in situ hybridization techniques or examined only fetal or newborn mice (22,25). We propose that, in Sim1ϩ/Ϫ adults, dysfunction of Sim1-expressing neurons in the PVN, LHA, or amygdala, rather than their absence, causes hyperphagia and obesity.…”
Section: Discussionmentioning
confidence: 83%
“…All these regions also express Mc4r (23). Previous studies that did not report Sim1 expression outside the PVN and SON used less sensitive in situ hybridization techniques or examined only fetal or newborn mice (22,25). We propose that, in Sim1ϩ/Ϫ adults, dysfunction of Sim1-expressing neurons in the PVN, LHA, or amygdala, rather than their absence, causes hyperphagia and obesity.…”
Section: Discussionmentioning
confidence: 83%
“…Consistent with this model, several members of the Atonal family are expressed in terminally differentiated cells (Morrow et al, 1999;Lee et al, 2000). In addition, recent studies have suggested a link between one Atonal family protein, NeuroD, and the neuroendocrine/endocrine signaling pathways that control energy balance (Nilaweera et al, 2002;Khoo et al, 2003), and disruptions in NeuroD are associated with the development of certain forms of type 2 diabetes (Malecki et al, 1999). Nevertheless, the importance of Atonal family proteins in the regulation or maintenance of neuropeptide and peptide hormone levels in fully differentiated cells in vivo has not been directly established.…”
Section: Introductionmentioning
confidence: 88%
“…Interestingly, hypothalamic NeuroD mRNA levels are reduced in obese ob/ob and food-deprived mice, suggesting a functional relationship in mature neurons between NeuroD and the neuroendocrine/endocrine signaling pathways that control energy balance (Nilaweera et al, 2002). NeuroD is also required for activity-dependent granule neuron dendritic growth in the intact rat cerebellar cortex (Gaudilliere et al, 2004), and Gal4-NeuroD chimeras can activate insulin promoter elements in response to glucose stimulation of cultured pancreatic beta cells (Khoo et al, 2003).…”
Section: Potential Dual Functionality Of Other Atonal Family Membersmentioning
confidence: 99%
“…cDNAs for mouse Agrp, somatostatin, Crh and Trh were cloned to pBluescript vector to generate digoxigenin-labeled riboprobes. Probes for Pomc, Ghrh, Mash1 and Dlx1 have been described previously (Nilaweera et al, 2002;McNay et al, 2006). The probes for Sf1 and Gad1 were kind gifts from Dr Holly Ingraham at the University of California, San Francisco (CA, USA) and Dr Jane E. Johnson at the University of Texas Southwestern (TX, USA), respectively.…”
Section: Immunohistochemistry and Ishmentioning
confidence: 99%